The Focus of Feminism: Challenging the Myths about the U.S. Women’s Movement - Cynthia Fuchs Epstein (Amnis)
This paper argues that the « second stage » of the woman’s movement in the United States has benefited working class and minority women as well as white women of the middle class from the time of its founding in 1966. By giving examples of the early agenda of the National Organization for Women it shows how it employed Civil Rights legislation to make employment practices more democratic throughout the class structure.